Glycopeptide Antibiotic Resistance Genes: Distribution and Function in the Producer Actinomycetes - Yushchuk, Oleksandr; Binda, Elisa; Marinelli, Flavia (Frontiers in Microbiology, 2020)
Glycopeptide antibiotics (GPAs) are considered drugs of ‘last resort’ for the treatment of life-threatening infections caused by relevant Gram-positive pathogens (enterococci, staphylococci and clostridia). Driven by the issue of the never-stopping evolution of bacterial antibiotic resistance, research on GPA biosynthesis and resistance is developing fast in modern “post-genomic” era. It is today widely accepted that resistance mechanisms emerging in pathogens have been acquired from the soil-dwelling antibiotic-producing actinomycetes, which use them to avoid suicide during production, rather than being orchestrated de novo by pathogen bacteria upon continued treatment. Actually, more and more genomes of GPA producers are being unravelled, carrying a broad collection of differently arranged GPA resistance (named van) genes. In the producer actinomycetes, van genes are generally associated with the antibiotic biosynthetic gene clusters (BGCs) deputed to GPA biosynthesis, being probably transferred/arranged together, favouring a possible co-regulation between antibiotic production and self-resistance. GPA BGC-situated van genes have been also found in metagenomics samples and searching in public databases of bacterial genomic information. Interestingly, some BGCs for antibiotics, seemingly unrelated to GPAs (e.g. feglymycin), carry van gene homologues. Herein, we would like to cover the recent advances on the distribution of GPA resistance genes in genomic and metagenomics datasets related to GPA potential/proved producer microorganisms. A thorough understanding of GPA resistance in the producing microorganisms may prove useful in the future surveillance of emerging mechanisms of resistance to this clinically relevant antibiotic class.